Run to the board game: Its implementation in teaching English vocabulary - Sharifah, Ferly; Megawati, Fika; Novita, Dian; Astutik, Yuli (Universitas Islam Malang, 2024)
In the era of globalization, mastering English is crucial for international communication. However, the success of English education in Indonesia is often hindered by limited language skills, particularly in vocabulary, which significantly affects students' comprehension. This challenge underscores the importance of fostering students' motivation to learn, as motivation serves as a key driver for academic success. This study employed a qualitative case study approach to investigate the implementation of the